Development of University Students’ Foreign Language Competence - Ozoda Abduvakhitovna, Suyunova; Iroda Makhmudzhanovna, Jalolova; Barnohon Masharipovna, Nazarova; Sardorhon Abdullaevich, Sagdullakhodjaev; Malika Mehriddinovna, Khusamiddinova (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with the peculiarities of foreign language education within professional training of specialists in higher education. The specificity of the program content of the language disciplines is revealed.